Perceived barriers, benefits, facilitators, and attitudes of health professionals towards type 2 diabetes management in Oujda, Morocco: a qualitative focus group study - Usman Sani Dankoly; Dirk Vissers; Souad Ben El Mostafa; Abderrahim Ziyyat; Bart Van Rompaey; Paul Van Royen; Abdellatif Maamri (BMC, 2023)
Abstract Background In Morocco, the treatment of type 2 diabetes (T2D) is mainly focused on medication and only 2% of patients are coached towards a healthier lifestyle. In Oujda, Eastern Morocco the prevalence of T2D is 10.2%, and the current trend is alarming, especially for women. Therefore, the aim of this study is to explore healthcare professionals (HCP) views on the perceived barriers and benefits of an integrated care approach in primary healthcare centers (PHCCs) to T2D management in Oujda. Methods A qualitative descriptive study using focus groups in 8 PHCCs. This resulted in a sample of 5 doctors and 25 nurses caring for diabetes patients. The transcripts of all conversations were coded to allow for thematic analysis. Results The participants mentioned different barriers to an integrated approach to DM management:: excessive workload; poor reimbursement policy; lack of staff and equipment; interrupted drug supply; poor working environment; limited referral; gap in the knowledge of general practitioners; health beliefs; poverty; advanced age; gender; the use of psychotropic drugs. An integrated approach could be facilitated by simplified electronic records and referrals; uninterrupted free care; staff recruitment; continuous professional development; internships. Benefits: structured care; promotion of care in PHCCs; empowerment of self-management. Conclusion HCP views reflect the urge to strengthen the management of T2D in PHCCs. There is a need for HCP with expertise in physical activity and nutrition to solve the current gap in the multidisciplinary integrated care approach. The specific local context in this Eastern Moroccan region, with limited resources and remote hard-to-reach rural areas, can contribute to patients' reluctance to change their lifestyles, and is a challenge to provide care in an efficient and sustainable manner. More research is needed to see how a patient-centered multidisciplinary approach to T2D management can help motivate patients in Morocco to change to a healthier lifestyle.